Hepatotoxic Effects of Microcystis aeruginosa (PCC 7820) on Wister Rats - Manage, P.M.; Yasawardena, S.G.; Wedage, W.S. (My University, 2009)
The potential toxic effect of Microcystis aeruginosa through oral contamination is becoming important. The present study was carried out to find the possible hepatotoxic effects of toxic M. aeruginosa (PCC 7820) on male Wistar rats as animal model. Hepatotoxicity assessment 1vas done by estimation of serum hepatic enzyme levels of r-Glutamyl transferase (GGT). Alkaline phosphatase (ALP). Alanine aminotransferase (ALT/GPT), Aspartate aminotransferese (GOT/AST). Rat treated with non toxic (CYA -/3) and toxic non homogenized M. aeruginosa (PCC 7820) were normal in appearance where as rats receiving homogenized toxic M aeruginosa (PCC 7820) were lethargic and gained less weight which indicates a possible toxic effect on the test animals. The absolute and relative (% body weight) mean weight of liver and kidneys ofthe homogenous toxic M aeruginosa (PCC 7820) treated animal lj'ere lower than those who received non homogenized toxic M aeruginosa (PCC 7820) and the difference is statistically significant (p<0. 00J). Liver sections of rats receiving fresh toxic M aeruginosa and the homogenized toxic M aeruginosa did not show lymphatic infiltration or signs of necrosis. Rats treated 'with homogenized M aeruginosa showed lowering of absolute liver weight compared to the fresh M aeruginosa treated rats. Statisticcally significant (p<0.005) increase levels of serum y-Glutamyl transferase (GGT) was detected in rats 14 days after oral administration with homogenized toxic M aeruginosa (PCC 7820). There was no significant differentfound in serum Alanine aminotransferase (ALT/GPT) concentration between treated and control groups. The results indicate that prolonged oral administration of homogenized M. aeruginosa lead to functional hepatotoxicity in male Wister rats without evident histopathological liver necrosis.
Keywords: Toxic M aeruginosa; Wistar rats; Hepatotoxicity; Serum chemistry